2011
DOI: 10.1111/j.1539-6975.2011.01435.x
|View full text |Cite
|
Sign up to set email alerts
|

Pension Funds’ Asset Allocation and Participant Age: A Test of the Life‐Cycle Model

Abstract: This paper examines the impact of participants' age distribution on the asset allocation of Dutch pension funds, using a unique data set of pension fund investment plans for 2007. Theory predicts a negative effect of age on (strategic) equity exposures. We observe that pension funds do indeed take the average age of their participants into account. However, the average age of active participants has been incorporated much more strongly in investment behaviour than the average ages of retired or dormant partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 23 publications
4
46
1
1
Order By: Relevance
“…As of December 31, 2015 the mean duration of the bonds making up the Index was 8.45 years. 48 out of 60 bonds had a high grade credit rating 6 , while the rest of the 12 bonds had an upper medium grade credit rating.…”
Section: Data Description and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…As of December 31, 2015 the mean duration of the bonds making up the Index was 8.45 years. 48 out of 60 bonds had a high grade credit rating 6 , while the rest of the 12 bonds had an upper medium grade credit rating.…”
Section: Data Description and Methodologymentioning
confidence: 99%
“…Moreover, the use of these data may be justified by the fact that return and volatility rates we employ (reported in table 2) are comparable to (or perhaps slightly higher than) the respective rates usually reported for the developed markets over much longer periods (e.g., Dimson et al, 2014). 6 According to Maalot credit rating agency estimates. Table 3 reports the correlations between the returns of the four major asset classes.…”
Section: Data Description and Methodologymentioning
confidence: 99%
“…The risky assets in this study combined quoted, unquoted and private equities and offshore investment, a better representation of investment strategy than previous studies. The studies reviewed on determinants of pension scheme investment strategy were carried out in mature pension markets of America (Chemla, 2005;Lucas &Zeldes, 2009), andEurope (Gerber& Weber, (2007) and Bikker, Broeders &Hollanders (2012)). The study sought to fill the regional gap by carrying out the study in emerging pension markets in and Kenya in particular.…”
Section: In the 21mentioning
confidence: 99%
“…The results indicated that scheme design did not influence strategic equity exposure. Reid (2014) extended the study by Bikker et al, (2012) by investigating factors that influenced Dutch pension schemes' strategic risk exposure. Using annual financial data from 110 Dutch pension schemes for the period 2011 and 2012 and found evidence that defined benefit schemes had a higher strategic risk exposure compared to defined contribution and hybrid pension schemes.…”
Section: Effect Of Scheme Design On Investment Strategymentioning
confidence: 99%
“…[21] empirically analyzed the capital cost of enterprise pension plan and financial constraints. [22] used the Life Cycle Model to research the assets allocation and contribution period of the pension. [23] analyzed the influence of pension system towards companies and finance.…”
Section: Introductionmentioning
confidence: 99%